Frontiers of Pattern Recognition: The Proceedings of the International Conference on Frontiers of Pattern Recognition - Watanabe, Satosi (Academic Press, 2014)
Frontiers of Pattern Recognition contains the proceedings of the International Conference on Frontiers of Pattern Recognition which took place on January 18-20, 1971, at the University of Hawaii, Honolulu.The compendium consists of 30 papers from authorities from eleven different countries, which describe the frontiers of pattern recognition as viewed from diverse viewpoints. Topics discussed include some techniques for recognizing structures in pictures, grammatical inference, syntactic pattern recognition and stochastic languages, and pattern cognition and the organization of information. Also covered are subjects on human face recognition, cluster analysis, and learning algorithms of pattern recognition in non-stationary conditions.Computer scientists, mathematicians, statisticians, linguists, and psychologists will find the book informative.